Multi-criteria Evaluation + Positional Ranking Approach for Candidate Selection in E-voting - Yusifov, Farhad; Alguliyev, Rasim; Aliguliyev, Ramiz (Decision Making: Applications in Management and Engineering, 2019)
E-voting is one of the most important components of e-democracy and includes interesting research topics, such as the mechanisms of participation in elections, technological solutions to e-voting and the efficient application of those in e-voting. Currently, there are numerous voting systems adopted in many countries of the world and each of those has specific advantages and problems. The paper explores the e-voting system as one of the main tools of e-democracy and analyzes its advantages and drawbacks. Voting results always lead to a broad debate in terms of candidate selection and of whether the candidate elected to a position is suitable for that position. At present, the selection of qualified personnel and their appointment to responsible positions in public administration is one of the topical issues. In the paper, multi-criteria decision-making (MCDM) is proposed for the selection of candidates in e-voting. The criteria for candidate selection are determined and the relationship of each candidate with the other candidates is assessed by using a binary matrix. The candidate rank is calculated according to all the criteria. In a numerical experiment, candidate evaluation is enabled based on the selected criteria and ranked by using a positional ranking approach. The proposed model allows for the selection of a candidate with the competencies based on the criteria set out in the e-voting process and the making of more effective decisions as well.